TRANSFORMATION OF MARKETING TECHNOLOGIES IN MACHINE INTELLIGENCE ERA - V. Starostin (Вестник университета)
Modern marketing becomes more technologically advanced. First of all, this is the result of popularity of digital devices and rapid growth of computational power of computers. It allows to digitalize consumers’ofline behavior and to analyze data using machine learning methods in order to enhance the relevance of particular marketing programs for each individual customer segment. This article reviews how traditional marketing technologies are transformed to reflect the potential of artificial intelligence and machine learning.